Near death: life and dominance in rio de janeiro and medellin (2014)
This article takes two cities, Rio and Medellin, to show the relationship between power and social tissue. In the first part, the text analyzes the administration of violence as a means of establishing an order headed by the symbolic framing of approaching death. In a next part, take the other side of the power, the pursuit of "consensus" and legitimacy. Then we look at the efforts and results to eradicate the problem. Finally, it considers the impacts on social arrangements and outlines possible action against the two axes of mafia power: social integration and economic compensation.